2018
DOI: 10.5194/acp-18-14059-2018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of urban canopy meteorological forcing on aerosol concentrations

Abstract: Abstract. The regional climate model RegCM4 extended with the land surface model CLM4.5 was coupled to the chemistry transport model CAMx to analyze the impact of urban meteorological forcing on surface fine aerosol (PM2.5) concentrations for summer conditions over the 2001–2005 period, focusing on the area of Europe. Starting with the analysis of the meteorological modifications caused by urban canopy forcing, we found a significant increase in urban surface temperatures (up to 2–3 K), a decrease of specific … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
48
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(66 citation statements)
references
References 81 publications
17
48
1
Order By: Relevance
“…Higher urban temperatures in connection with UHI directly modify chemical reaction rates and aerosol nucleation as well as indirectly modify dry deposition and wet scavenging rates (Seinfeld and Pandis, 1998). Although higher temperatures favor ozone formation (Im et al, 2011), in urban areas, the situation can be different. Huszar et al (2018a) showed that due to higher temperatures alone, surface ozone in urban areas is reduced, while the main contribution is given by increased dry deposition velocities and increased flux of nitrogen oxides (NO x ) towards nitric acid (HNO 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Higher urban temperatures in connection with UHI directly modify chemical reaction rates and aerosol nucleation as well as indirectly modify dry deposition and wet scavenging rates (Seinfeld and Pandis, 1998). Although higher temperatures favor ozone formation (Im et al, 2011), in urban areas, the situation can be different. Huszar et al (2018a) showed that due to higher temperatures alone, surface ozone in urban areas is reduced, while the main contribution is given by increased dry deposition velocities and increased flux of nitrogen oxides (NO x ) towards nitric acid (HNO 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…As the urban canopy meteorological forcing (UCMF) induced NO 2 changes are caused primary by vertical turbulence transport (Huszar et al, 2020), the amount of removed material (i.e., the NO 2 ) is expected to be proportional to the absolute amount of that material. This could explain the larger change for the high end of the distribution.…”
Section: Dmax8ho3 (%)mentioning
confidence: 99%
“…In summary, the urban canopy layer forces the air within and above the canopy layer towards modified physical properties (temperature, humidity, wind speed, etc. ), and therefore we adopt here the term "urban canopy meteorological forcing" (UCMF) introduced recently by Huszar et al (2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors response: Our paper is based on previous research made to investigate the role the urban canopy plays in controlling the city scale meteorological conditions and consequently the chemistry and transport of pollutants. The mutual links between meteorology and gas-phase chemistry (NOx-ozone) in urban areas is detailed in Huszar et al(2018a), whereas in Huszar et al(2018b) we extended this analysis to primary and secondary aerosols. Finally in Huszar et al(2020), after identifying that vertical eddy transport plays the most important role, we focused on this aspect of the urban canopy meteorological forcing on chemistry.…”
mentioning
confidence: 99%